Evolution and consumer psychology. Issue 1 (16th December 2017) - Durante, Kristina M.; Griskevicius, Vladas
Abstract: An evolutionary theoretical approach considers the adaptive function of behavior. Here we discuss what it means to use an evolutionary approach to generate predictions about consumer behavior and the value of applying an evolutionary lens to the study of consumer psychology. We begin with a discussion of the core insights of evolutionary theory and the common misperceptions associated with an evolutionary approach to the study of behavior. We then detail how specific evolutionarily informed theories can be applied to four core areas of consumer research: risk preference, competition and luxury consumption, self‐control and temporal preferences, and the consumer behavior of women and families. We also discuss the strengths and limitations of an evolutionarily informed research program.